Successful treatment of metastatic pheochromocytoma in the spine with cement augmentation - Cai, Siyi (Medicine (Baltimore), 2017)
Metastatic pheochromocytoma in the spine is rare, and there is no standard curative management. Treatment via open surgery is often risky in the perioperative period, while osteoplasty by cement augmentation is a less invasive option. We describe 2 patients with recurrence of pheochromocytoma involving the spine and the pelvis who were successfully treated with osteoplasty by cement augmentation. A 31-year-old female underwent cement augmentation for a pelvic lesion 6 months after the resection and screw fixation of an L3 lesion. A 58-year-old male underwent cement augmentation to directly destroy the functional tumor, with a surgical decompression 6 months later. Both patients showed appropriate destruction of the tumor, adequate pain relief, and the decreased release of catecholamine from metastatic lesions. Osteoplasty by cement augmentation may be a treatment option for patients with metastatic pheochromocytoma who cannot undergo appropriate surgery or decline surgery. This represents a safe approach to sustainably relieve pain and stabilize vertebral bodies with metastatic malignant pheochromocytoma.